Analysis of Digital Marketing and Green Marketing Strategies to Maintain Business Sustainability on MSMEs Bandung Regency in Digital Era - Rachmawati, Dwi; Wijaya, Hadi; Pambreni, Yuni (Journal of Applied Business Administration, 2023)
This study aims to find out the influence of Digital Marketing and Green Marketing on marketing performance and Sustainability Business of MSMEs Bandung regency. With the number of respondents as many as 100 MSMEs actors. The instrument in the questionnaire is measured using a Likert scale (5 scales), while the variables are 1) Independent Variables consisting of Digital Marketing and Green Marketing, 2) Dependent Variable is Sustainability Business, 3) Mediating Variable is Marketing Performance analysis used in this study is path analysis. The results show that only Digital Marketing and Green Marketing has positive influence on sustainability business of MSMEs Bandung regency through marketing performance.